CHRNE Mutation and Congenital Myasthenia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The CHRNE e1293insG mutation was identified in 14 (60%) of 23 North African families with an early onset form of congenital myasthenic syndrome studied at centers in France, Tunisia, Algeria, and UK.